Assessment of the Levels of Radiation Absorbed By Radiology Personnel in Some Hospitals in Makurdi Metropolis - J.T, Iortile; B.E, Archibong; J.T, Chelen (International Journal of Natural Sciences Research, 2013)
The levels of radiation of radiology personnel were assessed in five major hospitals in Makurdi metropolis. A data collection instrument was a semi structured self-completion questionnaire, designed in line with the objectives of the study. Personnel radiation monitoring was available in only 1 out of 5 hospitals (20%). Radiation monitors were found to be fairly read about every quarter of the year only in one (1) hospital. Radiation safety officers were available in only 3 hospitals (60%). About (32.5%, n=13) believe the hospital management do not make provision for it. Dosimetric records of staff were not given any consideration in the establishment of radiology departments. Personnel radiation monitoring in Hospitals on the whole was found to be very poor. This is a significant precautionary lapse as radiation risk cannot be assessed and corrective measures taken.